Production Functions in Which the Elasticities of Substitution Stand in Fixed Proportion to Each Other: A Comment - Ramanujam, M. S. (Review of Economic Studies, 1967)
Production Functions in which the Elasticities of Substitution stand in Fixed Proportion to Each Other: A Comment Get access M. S. Ramanujam M. S. Ramanujam Delhi School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 4, October 1967, Page 432, https://doi.org/10.2307/2296564 Published: 01 October 1967